Establishing the weighting of possession ending free throws for FIBA men`s World Cup - Lan, Y. C.; Liu, Y. T. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: In basketball, points per possession measures the performance efficiency. Although the number of possessions in a game is not usually recorded on the box scores, the number of field-goal-attempts (FGA), offensive-rebounds (OREB), turnovers (TOV), and free-throw-attempts (FTA) found on common box score data can be used to estimate the number of possessions in a game. The possession-ending free throws is only a fraction of the number of free throws that is not identifiable from the box score, and the commonly used weighting (?) of 0.44 was based on the data from NBA (Kubatko et al., 2007). The purpose of the study was to examine the ratio of possession-ending free throws to the total number of free throws in a game for the FIBA men`s world cup and to compare the recorded number of possessions to the estimated number of possessions from the box score data.